Effect of Integrated Nutrient Management on Soil Enzymes, Microbial Biomass Carbon and Soil Chemical Properties after Eight Years of Rice (Oryza sativa) Cultivation in an Aeric Endoaquept - A. Gayan, Y.B. Devi; B. Bhattacharyya, D.J. Nath*, D. Gogoi, S. Buragohain (Journal of the Indian Society of Soil Science, 2016)
Soil enzymes, microbial biomass carbon (MBC), microbial population and selected soil chemical properties were evaluated in a field experiment involving integrated nutrient management (INM) for eight years of rice cultivation in an Aeric Endoaquept. Persistent application of biofertilizers for eight years illustrated the clear increase in fluorescein di-acetate (FDA) hydrolase (10.51 µg fluorescein g-1 h-1) and arylsulfatase (ARS) (43.8 µg p-nitrophenol g-1 h-1) activities with 50% of NP fertilizer. Application of enriched compost (EC) (2 t ha-1) demonstrated clear increase in dehydrogenase (DH) (220.0 µg TPF g-1 d-1) and phosphomonoesterase (PME) (388.8 µg p-nitrophenol g-1 h-1) activities with only 25% of recommended nitrogenous (N) and phosphatic (P) fertilizer. The integration of biofertilizers or EC with reduction of 75 to 50% NP fertilizers resulted the higher MBC in between 270.6 and 323.3 µg g-1 compared to chemical fertilizer alone. Similarly, maximum accretion (11.2 g kg-1) of organic carbon (OC) was observed with the application of EC (1 t ha-1) amid sizeable cut (50% NP) of chemical fertilizers after eight crops. Abundance of Azospirillum (5.76 to 5.84 log cfu g-1) and PSB (5.82 to 5.90 log cfu g-1) were observed with application of either biofertilizers or EC (1 t ha-1) and 50% NP fertilizers. The MBC and OC displayed significant correlation with intracellular and extracellular soil enzymes and microbial populations in rice soil following INM. The overall multifaceted effects of different INM treatments facilitated beneficial soil conditions in the present study reflected the significant increase in the grain yield of rice (4.07 t ha-1) which is equivalent to the 100% NPK (3.86 t ha-1). The application of biofertilizers with 50% NP showed highest value (234.3 kg ha-1) of available N, whereas highest available P (25.8 kg ha-1) was obtained in the INM treatment that contained EC (2 t ha-1).